miR‐944 inhibits metastasis of gastric cancer by preventing the epithelial–mesenchymal transition via MACC1/Met/AKT signaling - Pan, Tao (FEBS Open Bio, 2017)
MicroRNAs (miRNAs) are reported to play vital roles in tumor progression. Recently, miR‐944 was reported to play either an oncogenic or tumor suppressive role in human cancers. However, the expression of miR‐944 and its exact role in gastric cancer (GC) remain unknown. This study aimed to evaluate whether loss of miR‐944 could promote the epithelial–mesenchymal transition (EMT) of GC. Reduced expression of miR‐944 was identified in 40 pairs of human GC and matched normal tissues by qRT‐PCR. Reduced expression of mi‐944 was also observed in GC cell lines. Restoration of miR‐944 inhibited cell migration and invasion in MGC‐803 cells, while its loss facilitated metastasis of SGC‐7901 and BGC‐823 cells. Notably, miR‐944 overexpression prohibited EMT of GC cells in vitro, while miR‐944 knockdown had the opposite effect. Bioinformatics software predicted that MACC1 was a direct target of miR‐944. We observed negative regulation of miR‐944 on MACC1 expression, and direct binding between miR‐944 and MACC1 was verified by dual‐luciferase assays in HEK293T cells. Restoration of MACC1 resulted in promoted EMT and metastasis in miR‐944‐overexpressing MGC‐803 cells. Loss of MACC1 abrogated the effects of miR‐944 knockdown on EMT and metastasis of SGC‐7901 cells. We also found that the Met–AKT pathway might be involved in MACC1‐mediated EMT. In conclusion, miR‐944 acts as an inhibitor of EMT and metastasis of GC by targeting MACC1. This study highlights the potential effects of miR‐944 in the prognosis and treatment of GC.